2022
DOI: 10.4102/hsag.v27i0.1693
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers’ leadership roles in mining primary healthcare settings in Gauteng

Abstract: Background: Nurse managers carry the light of leadership in mining primary healthcare settings (mPHCs). They must ensure that this light shines for their followers to improve the quality of service rendered in primary healthcare. However, the nurse managers in mPHCs are confusing their leadership roles with management roles. The existing policies such as operational management of mPHCs are also not clarifying the leadership roles of nurse managers.Aim: The purpose of this study was to understand the nurse mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Jooste ( 2017 :205) and Nene ( 2022 ) revealed that it was also difficult for OMs to inspire their nurses, and they were all expected to do more than their capacity, and one cannot lead and follow at the same time. As the numbers of patients who were coming to PHC facilities for services were increasing in South Africa, no new staff members were employed to close the capacity (Brouer et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jooste ( 2017 :205) and Nene ( 2022 ) revealed that it was also difficult for OMs to inspire their nurses, and they were all expected to do more than their capacity, and one cannot lead and follow at the same time. As the numbers of patients who were coming to PHC facilities for services were increasing in South Africa, no new staff members were employed to close the capacity (Brouer et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The management of the PHC clinics of Ekurhuleni had to acknowledge that the OMs interpret change differently, and for effective change implementation, they had to be supported, irrespective of their category -whether they were early adopters, early or late majority. Jooste (2017:205) and Nene (2022) revealed that it was also difficult for OMs to inspire their nurses, and they were all expected to do more than their capacity, and one cannot lead and follow at the same time. As the numbers of patients who were coming to PHC facilities for services were increasing in South Africa, no new staff members were employed to close the capacity (Brouer et al, 2016).…”
Section: Budgetary Cuts and Increasing Demands On Resourcesmentioning
confidence: 99%
“…From a nursing perspective, clinical leaders influenced care delivery systems through engagement in policy development at all levels of government [1,11], but these perspectives are less documented in the HIV context. Similarly, there is confusion in clinical leadership roles in distinguishing between managerial, resource management, and clinical roles [12].…”
Section: Introductionmentioning
confidence: 99%
“…El Sayed and Sleem ( 2011 ) and Mahboube et al ( 2019 ) posit that positive working relationships between nurses and doctors is considered the main factor in achieving positive medical results, which is the ultimate goal of the healthcare system. Hoseini ( 2009 ) and Nene ( 2022 ) attest that nurses and doctors should effectively and efficiently establish communication and believe that neither can achieve the desirable goal alone; in other words, they should take necessary steps towards creating positive workplace relationships to promote teamwork.…”
Section: Introductionmentioning
confidence: 99%